EFEKTIVITAS STRATEGI KOMUNIKASI KONSTRUKSI INDONESIA 2013 - Nantia Rena Munggaran (Dialektika, 2016)
Construction Indonesia is a program of activities undertaken by the Government as the organizer of the government which, besides acting as financial manager, the government carry out the mandate of the people to use the money for the benefit of the people of Indonesia. Countries, particularly Indonesia have valuable assets or property on Natural Resources self contained and has, not least on the wealth of assets Human Resources (HR) of his. Given the budget for the electronic media (television and radio) is quite large, to 'hook' of electronic media as a media partner. Another thing you can do is make some sort of event / talk show that is not only heard or seen at a glance by the audience and the information presented can be fully delivered. Talkshow material can also be packaged with a material that is loaded with educational aspects.